Experiments on Laguerre‐Gaussian modes selection in ceramic lasers. Issue 6 (6th May 2013) - Senatsky, Yu.; Bisson, J.‐F.; Li, J.; Shirakawa, A.; Thirugnanasambandam, M.; Ueda, K.; Palashov, Oleg V.; Khazanov, Efim A.; Kravchenko, Valery B.; Fedorov, Pavel P.
Abstract A study on Laguerre‐Gaussian (LG) modes selection in cw and pulsed Nd:YAG or Yb:YAG ceramic lasers pumped by diodes or an external laser source was carried out. Methods of scalar and vector LG modes selection from low to high orders, involving shaping of the pump profile, usage of intra‐cavity lenses, uniaxial crystals and polarization selective mirrors, are considered. CCD camera images of beam profiles of hollow scalar LGpm modes (p ‐radial, m ‐azimuth indices) of record high‐orders and Bessel‐like multi‐ring modes with highly directional propagation properties are presented. CW and pulsed ceramic lasers with radially or azimuthally polarized LG vector modes of low and high orders are also demonstrated. Applications of the developed laser schemes and LG beams are discussed. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)